Public Transport Integration Into Urban Planning - Marija Burinskienė; Rasa Ušpalytė-Vitkūnienė; Faustina Tuminienė (The Baltic Journal of Road and Bridge Engineering)
Growth of towns is a result of citizen’s social and physical division. Urban planners and scientists have increased the number of links between urban transport and urban development. Public transport has been in the focus of attention as a sustainable and environmentally sensitive transport that brings environmental benefit and possibility to serve mobility needs of citizens without private cars and reduces social division. The article identifies the main factors that affect the use of public transport in town: land use planning; local government policy; extent of economic resources; implementation of modern technologies; social tendencies. Analysis of the scientific literature has revealed four main models of towns of sustainable urban forms: neo-traditional development, urban restrictions, compact town and ecological town. Vilnius has the formed urban and mono-functional structure with a high imbalance between residential and work places which conditions a high mobility of inhabitants as well as high concentration of transport flows on limited-density street networks between the western residential areas and the central part of the City where the main workplaces are located. It presents the provisions of the Vilnius City Master Plan 2015 concerning the public transport improvement. The article also assesses developments in the public transport network in 2003–2009 resulting from changes in individual routes with regard to passenger time necessary for traveling. Modelling is carried out with the help of VISUM software. Citizens of Buivydiškės and Santariškės are mostly affected by the developments, while the situation in Pavilnys, Aukštieji Paneriai and Tarandė has changed only slightly.